Evolucion de la flora arvense en olivares mantenidos en no-laboreo y tratados con Simazina o Diuron - Saavedra, M.=700 1 Pastor, M.
(Es, En)
ilus., 9 ref.
Keywords: ESCARDA; CERO-LABRANZA; ACEITUNA; EVOLUCION; FLORA; CONTROL QUIMICO; HERBICIDAS; SIMAZINA; DIURON; ESPAÑA; NO-LABOREO